2018
DOI: 10.3992/1943-4618.13.2.98
|View full text |Cite
|
Sign up to set email alerts
|

The Indoor Environmental Quality Performance of Green Low-Income Single-Family Housing

Abstract: There is little empirical evidence in the literature about the indoor environmental quality performance of residential buildings in general and of social housing in particular. To address this problem, this study used a mixed-method approach to evaluate the indoor environmental quality performance of 17 green low-income single attached family houses in Brandon, Manitoba, Canada. Questionnaires were administered to occupants to assess their snapshot and long-term satisfaction with the indoor environment. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…Green building performance has been the focal point of a number of studies and assessments in the course of the last decade. There is a broad literature on the subject analysing green buildings from economic, environmental and social perspectives, and studying the relationship between indoor environmental quality and its effect on productivity and health [10,[21][22][23][24][25][26][27][28][29]. However, the focus on acoustic quality has been restrained and mainly limited to commercial and education facilities.…”
Section: Green Buildings and Acoustic Quality Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Green building performance has been the focal point of a number of studies and assessments in the course of the last decade. There is a broad literature on the subject analysing green buildings from economic, environmental and social perspectives, and studying the relationship between indoor environmental quality and its effect on productivity and health [10,[21][22][23][24][25][26][27][28][29]. However, the focus on acoustic quality has been restrained and mainly limited to commercial and education facilities.…”
Section: Green Buildings and Acoustic Quality Studiesmentioning
confidence: 99%
“…Akom et al [26] investigated 17 green low-income single attached family houses in Brandon, Canada. The findings showed that the majority of measured A-weighted BN levels were under 50 dB(A), with variation between 27.7 and 75.3 dB(A), recording marginally higher levels in living rooms than in bedrooms, and the analysis indicated a statistically significant difference in means of background noise levels across the different spaces.…”
Section: Green Buildings and Acoustic Quality Studiesmentioning
confidence: 99%
“…Popovic et al [39] consider that the evaluation of social criteria for a complex system is also done on health and comfort criteria. In a survey, Akom et al [40] determine that occupant satisfaction is related to indoor air quality, and that frequently used health criteria are Volatile Organic Components (VOCs) and Particulate Matters (PM). Although there is little data available on thermal comfort for EA, some studies use coefficients such as Standard Effective Temperature (SET) to assess comfort based on temperature, relative humidity and air velocity [41].…”
Section: The Decision Criteria For Relevant Use Of Eamentioning
confidence: 99%
“…representing 50% of the total inert waste in France [31]), whereas it can be revalued as construction materials, having, as seen above, the potential to regulate the indoor air quality (IAQ) and hydrothermal comfort. Earth material contains zero volatile organic compounds (VOCs) in contrast to many other materials (paint, adhesives, sealants, among others) affecting the IAQ and exposing occupants to health risks through a building's lifespan [32]. It was recently scientifically established (although already well known by end-users) that earthen architecture, when properly implemented in the construction phase, generates an excellent IAQ especially owing to its passive capacity for moisture buffering [33].…”
Section: A High-tech Multi-function Materials For Architecturementioning
confidence: 99%